Analysis of After-Sales Service Quality for Hotel Smart Lock Products Using the Servqual Method and Quality Function Deployment (QFD) - Sujiono, Sujiono; Krisnawati, Febrian (Syntax Literate, 2025)
The increasing demand for after-sales services for smart lock products in the hospitality sector has shown significant growth, reflecting the rising importance of smart lock technology in enhancing hotel image, safety, comfort, and guest privacy. PT. XYZ, a smart lock provider, recorded an increase in product and after-sales service issues during 2021–2023. This research aims to measure service quality using the SERVQUAL method to identify gaps between customer expectations and perceptions and to propose improvement strategies using Quality Function Deployment (QFD). A survey involving 60 respondents from various managerial positions in the hospitality industry was conducted, utilizing 15 SERVQUAL-classified attributes. The findings revealed five attributes with significant negative gaps, indicating weaknesses in the after-sales service provided. Importance-Performance Analysis identified RV3 and RL3 attributes as top priorities due to their high importance and low perceived performance. The QFD analysis revealed that proactive and routine inquiries into customer complaints and issues are the most critical improvements required, with the highest priority weight of 7,029. Active and responsive customer communication is essential for enhancing the quality of after-sales services for smart lock products in the hotel industry.